Properties of a Bacillus subtilis strain lacking DNA polymerase I - Villani, Giuseppe (1974)
We have isolated a mutant of Bacillussubtilis deficient in DNA polymerase I, denominated polA42, which shows a reduced ability to repair the damage to DNA by UV radiation, MMS and mitomycin C;the ability to perform recombination is not appreciably impaired.DEAE cellulose chromatography allows the separation of polymerases I and II from the parental strain;a simple procedure is also described which allows to separate rapidly the polymerases II and III of the mutant strain. The three separated polymerases have similar catalytic properties but they can be distinguished for their sensitivity to inhibitors: PCMB inhibits polymerases II and III but not polymerase I; HPUra inhibits only polymerase III. All three enzymes are unaffected by nalidixate. The DNA synthesis occurring in cells of the polA42 strain permeabilized with toluene is inhibited by nalidixate, whereas the synthesis occurring in polA(+) toluenized cells is unaffected by the drug. The polA gene has been mapped by transduction and localized between the phe(12) and argA(3) genes.